Synthesis of 1,3-cis-disubstituted sterically encumbered imidazolidinone organocatalysts - Wallbaum, Jan; Werz, Daniel B. (Beilstein Journal of Organic Chemistry, 2017)
A variety of novel imidazolidinone-based organocatalysts with bulky substituents were synthesized under mild reaction conditions starting from easily accessible substrates. Different natural and unnatural amino acid methyl amides were cyclized with aromatic carbaldehydes to yield two diastereomeric MacMillan-type catalysts. Special emphasis was put on bulky residues such as mesityl and pyrene moieties.
Keywords: imidazolidinone; MacMillan catalyst; organocatalysis